2011
DOI: 10.1177/1464884910388223
|View full text |Cite
|
Sign up to set email alerts
|

The immediacy of online news, the visibility of journalistic processes and a restructuring of journalistic authority

Abstract: Transparency has been emphasized as a new norm within journalism and has received a great deal of attention. The credo of transparency is openness, and the interactive potential of digital media has been identified as one key element in achieving openness. In this essay it is argued that by exposing previously hidden journalistic processes, the high speed of online news plays a part in this orientation towards transparency in journalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 40 publications
2
121
0
17
Order By: Relevance
“…However, the effects are not totally absent, although few and small, and when they occur the findings suggest that they indeed, as previous research suggests (Gillmor, 2004;Karlsson, 2011;Kovach & Rosenstiehl, 2001), have a positive effect on how the audience perceive journalism and news. Links in particular seem important as effects of those could be found in both source and message credibility.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…However, the effects are not totally absent, although few and small, and when they occur the findings suggest that they indeed, as previous research suggests (Gillmor, 2004;Karlsson, 2011;Kovach & Rosenstiehl, 2001), have a positive effect on how the audience perceive journalism and news. Links in particular seem important as effects of those could be found in both source and message credibility.…”
Section: Discussionsupporting
confidence: 65%
“…This theoretical proposal also have an empirical dimension as research has shown that online journalism is being actually produced along transparency rather than objectivity criteria (see Karlsson, 2011, for an overview of the arguments). In a review by Karlsson (2010) on previous transparency research two different forms of transparency is suggested -disclosure and participatory transparency.…”
Section: Routines Norms and Credibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Normative theories, which undergirded the earliest efforts to conceptualize journalism by scholars (Wahl-Jorgensen and Hanitzsch 2013) as well as practitioners, also face new challenges. Is transparency the new objectivity, as some have suggested (Karlsson 2011;Hellmueller et al 2013)? Is interaction replacing independence, or can they somehow co-exist?…”
Section: Journalism Studiesmentioning
confidence: 97%
“…Erixon, 2010;Metzger & Flanagin, 2008), journalism (cf. Hayes, Singer, & Ceppos, 2007;Karlsson, 2011), politics (cf. Loader & Mercea, 2012;Nilsson & Carlsson, 2013) and so on how traditional structures of authority are being negotiated.…”
Section: Introductionmentioning
confidence: 99%